The Moderating Effect on Community Intention to Believe in Excellent Islamic Schools Education - Marjukah, Anis; Nugroho, Arif Julianto Sri; Haris, Abdul; Jati, Agung Nugroho; Almasitoh, Ummu Hany (Letiges, 2024)
This research aims to describe and test the independent variables of attitude, subjective norms and self-efficacy, which can influence people's motivation to send their children to excellent Islamic primary and secondary Schools with two moderating variables, Trust and Service involvement. The research design is quantitative survey research. The sampling technique was carried out by purposive sampling. The research respondents were a community in Klaten Regency who intended to send their children to a number of excellent Islamic primary and secondary Schools, with a total number of 110 respondents. The Structural Equation Model test is used in research to simultaneously test the relationship between variables. The results of the validity, reliability and goodness of model tests are declared fit and proven that there is a direct influence of attitude values, subjective norms and cell-efficacy on intentions. The moderating test of the trust and service-involvement variables can strengthen the emotional norm attitude and self-efficacy variables on parents' choices to send their children to excellent Islamic schools. In the future, excellent Islamic schools must maintain or further increase public trust in the quality of learning services. The increasing rate of excellent Islamic primary and secondary education services leads to increasing competitive excellence.